2013
DOI: 10.1371/journal.pone.0077394
|View full text |Cite
|
Sign up to set email alerts
|

Large Extracellular Loop of Tetraspanin as a Potential Vaccine Candidate for Filariasis

Abstract: Lymphatic filariasis affects nearly 120 million people worldwide and mass preventive chemotherapy is currently used as a strategy to control this infection. This has substantially reduced the incidence of the infection in several parts of the world. However, a prophylactic vaccine would be more effective in preventing future infections and will supplement the mass chemotherapy efforts. Unfortunately, there is no licensed vaccine available currently to prevent this infection. Molecules expressed on the surface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 53 publications
0
30
0
Order By: Relevance
“…In vitro ADCC assay was performed as described previously [14, 33, 34]. Briefly, in a 96-well culture plate (Becton Dickinson, Franklin Lakes, New Jersey,USA), approximately 10–20 L3 of B. malayi were cultured in triplicates with 0.2 × 10 6 PBMCs (collected from a normal healthy human volunteer) and 50 μl each of pooled EN, MF, CP and NEN sera or protein-depleted EN, MF and CP sera.…”
Section: Methodsmentioning
confidence: 99%
“…In vitro ADCC assay was performed as described previously [14, 33, 34]. Briefly, in a 96-well culture plate (Becton Dickinson, Franklin Lakes, New Jersey,USA), approximately 10–20 L3 of B. malayi were cultured in triplicates with 0.2 × 10 6 PBMCs (collected from a normal healthy human volunteer) and 50 μl each of pooled EN, MF, CP and NEN sera or protein-depleted EN, MF and CP sera.…”
Section: Methodsmentioning
confidence: 99%
“…Both have a VaxiJen score close to 0.7 and above the threshold of 0.5, indicating their potential as novel antigens. Tetraspanin proteins have been investigated as vaccine target against other organisms such as the parasitic nematode Brugia malayi (Dakshinamoorthy et al, 2013). For the latter organism, this targeted tetraspanin is present on the outside of the nematode and the vaccine resulted in an almost 64% protection (Dakshinamoorthy et al, 2013).…”
Section: Implication For Tick Controlmentioning
confidence: 99%
“…Tetraspanin proteins have been investigated as vaccine target against other organisms such as the parasitic nematode Brugia malayi (Dakshinamoorthy et al, 2013). For the latter organism, this targeted tetraspanin is present on the outside of the nematode and the vaccine resulted in an almost 64% protection (Dakshinamoorthy et al, 2013). Members of this protein family were also tested against the helminth Schistosomes mansoni with a reduction of 57% and 64% for mean adult worm burdens and liver egg burdens for tetraspanin-1, respectively, and 34% and 52% for tetraspanin-2 (Tran et al, 2006).…”
Section: Implication For Tick Controlmentioning
confidence: 99%
“…There is a need for a more sustained approach such as a prophylactic vaccination to stop transmission and eliminate LF from the endemic areas (Dakshinamoorthy et al 2013c; Jambulingam et al 2016; Harris et al 2017). Our laboratory and others have identified several potential vaccine antigens that are shown to confer significant protection against challenge infections in experimental animals (Samykutty et al 2010; Dakshinamoorthy et al 2013b, Dakshinamoorthy et al 2013c; Arumugam et al 2014). One of our recent trials in non-human primates using a trivalent fusion protein vaccine (r Bm HAT) showed that approximately 40% protection could be achieved in vaccinated animals against a challenge infection (Dakshinamoorthy et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The only difference here is that we replaced the tetraspanin large extracellular loop (TSP) sequence in the r Bm HAT with thoredoxin peroxide-2 (TPX-2) to make the r Bm HAX multivalent construct. The rationale for this switch is based on our previous publication, where we show that TPX-2 is a potent inducer of Th1 responses (Gnanasekar et al 2004; Anand et al 2008) and the percent of protection conferred with r Bm TPX-2 is better than r Bm TSP (Anand et al 2008; Dakshinamoorthy et al 2013b). In the present study we evaluated the vaccine potential of r Bm HAX along with AL019 and MCA adjuvants.…”
Section: Introductionmentioning
confidence: 99%